Bahasa Inggris - Hafriani; Muhammad Yani; Yuzar, Maya Ghufra; Darwani; Bahasa Indonesia; Bahasa Indonesia, Bahasa Indonesia (Jurnal PEKA (Pendidikan Matematika), 2025)
Mathematical creative thinking is one of the important abilities that students must have to be able to solve various problems, both mathematical problems and problems related to life. The reality in the field is that students still lack mathematical creative thinking skills because the learning that is carried out is less able to optimize the development of students' mathematical creative thinking processes. This study aims to determine students' mathematical creative thinking skills through treffinger learning and conventional learning. The approach used in this study is quantitative with a pretest-posttest design. The research sample consisted of 16 students in the experimental class and 18 students in the control class. Data were collected through a valid written test that can measure students' mathematical creative thinking skills. Data analysis used a mean difference test using the t-test (independent sample t-test). The results of the study showed that there was a difference in the mathematical creative thinking skills of students who were taught using the treffinger learning model and students who were taught using conventional learning, where the mathematical creative thinking skills of students who were taught using the treffinger model were better than students who received conventional learning. The positive impact obtained from the application of the Treffinger learning model is also inseparable from the teacher's ability to understand the characteristics and phases of the Treffinger learning model as well as the time and class management which is already very good.